Identifying pederasts by their knuckles - Fraile Rodríguez, Carla (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2025)
Biometrics has experienced exponential growth in recent decades due to society’s need for security and authentication. This growth has encompassed various fields, including law enforcement, where it is used in the identification of victims and perpetrators of a multitude of crimes, including child pornography. This crime is an exceptional type since it is evidence of another intrinsic crime: the sexual abuse of a minor. Unlike other offenders, many pedophiles choose to document the commission of the crime by means of photographs or vídeos. The complexity in identifying these individuals lies in their tendency to hide their faces behind the camera. Sometimes, however, their hands are visible in the images and vídeos they take. But, is a photo of a hand enough to identify a person?